Educational Leadership at Chinese Universities: Exploring New Perspectives from Postmodernism and Maslow’s Hierarchy of Needs - Cui, xuanwei (Rumah Riset Publisher, 2024)
Global economic integration and the ongoing advancement of information technology have brought about rapid and profound transformations in Chinese society. The growing population of postmodernist university students in China is one of the most important factors advancing societal progress. The thesis of the current study is that educators at Chinese universities should exercise transformational and participative leadership to assist their students in succeeding in life. The contribution of the current study lies in not only introducing both the theories of postmodernism and Maslow’s Hierarchy of Needs to the realm of higher education management in China but also adding to higher education’s theories of social psychology and offering a practical approach to leadership for higher education in China.